1994
DOI: 10.1111/j.1744-7348.1994.tb04157.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glucosinolates during crop development in single‐ and double‐low genotypes of winter oilseed rape (Brassica napus): I. Production and distribution in vegetative tissues and developing pods during development and potential role in the recycling of sulphur within the crop

Abstract: The distributions of glucosinolates and sulphur were measured in the vegetative and reproductive tissues in a series of single-and double-low cultivars of oilseed rape (Bienvenu, Ariana, Cobra and Capricorn) grown on a sulphur-sufficient soil at Rothamsted in 1987/88, and in crops of the cv. Libravo grown with none or 40 kg/ha of sulphur on a sulphur-deficient soil at Woburn in 1990/91.The glucosinolate measurements demonstrated large differences in the abilities of single-and double-low cultivars to synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 14 publications
8
48
1
3
Order By: Relevance
“…napus seeds, the content of the GSLs, mainly aliphatic type, decreases dramatically (Fieldsend and Milfor, 1994). However, change of progoitrin content (5.59-45.4%) as the predominating aliphatic GSLs during seedling period showed opposite trends with other aliphatic GSLs in our study.…”
Section: Gsl (Gluconasturtiin)contrasting
confidence: 70%
“…napus seeds, the content of the GSLs, mainly aliphatic type, decreases dramatically (Fieldsend and Milfor, 1994). However, change of progoitrin content (5.59-45.4%) as the predominating aliphatic GSLs during seedling period showed opposite trends with other aliphatic GSLs in our study.…”
Section: Gsl (Gluconasturtiin)contrasting
confidence: 70%
“…In leaves the glucosinolate content is high in young developing tissues, reaching a maximum at full leaf expansion and then declining (Porter et al, 1991). This turnover and metabolism of glucosinolates (via pathways yet to be established), points to a potential storage role for the compounds, though in rape the vegetative tissue glucosinoiates do not seem to provide a significant proportion of the glucosinolate sulphur later found in seeds (Fieldsend & Milford, 19946). In addition, a great many studies have found that glucosinolate accumulation can be 'induced' by a variety of factors, such as insect attack (Lammerink, MacGibbon & Wallace, 1984;Koritsas, Lewis & Fenwick, 1989;Birch, Griffiths & Smith, 1990), mechanical damage (Bodnaryk, 1992) and fungal infection (Doughty et al, 1991).…”
Section: Dei'elopmental and Induced Changes In Glucosinolate Contentmentioning
confidence: 99%
“…The low content of glucosinolates in the rape plant vegetation parts questions their supply function (Zhao et al 1993a, b, Fieldsend andMilford 1994), while the content of the total sulphur and sulphates in the leaves during maturing in the wrapping layers of the siliques of rape plants, reflects the nutritional status of rape plant in the best way.…”
Section: Glucosinolates As Sulphur Supplymentioning
confidence: 99%